The role of the spiritual environment in building civil society - Sayitmurodova Feruza; Safarova N.O (Zien Journals, 2022)
The purpose of this article is to discuss the construction of a highly enlightened civil society, the role and relevance of the spiritual environment, the development of youth spirituality for the spiritual environment's stability, ongoing reforms in this area, and legal spirituality. and give suggestions for how to improve legal literacy
Keywords: democracy; society; civil society; Farobi